Exclusive breast milk and types of complementary foods with nutritional status - Surniah; Hamdana; Arlin Adam; Andi Alim (Institute of Computer Science (IOCS), 2023)
Malnourished children will have low brain capacity or an empty brain phenomenon that will impact the quality of human resources. One of the factors that cause malnutrition in children is that children do not get exclusive breastfeeding and receive complementary foods not according to their age. This study aims to determine the relationship between exclusive breastfeeding and complementary feeding with the nutritional status of children aged 4-7 months in the Working Area of ​​the Palakka Public Health Center, Barru District, South Sulawesi Province, Indonesia. This study used an analytic survey with a cross-sectional study design. Data was taken by total sampling from 54 children aged 4-7 months. Data on exclusive breastfeeding and types of complementary foods related to children's nutritional status using the Chi-Square test. This study showed that there was no relationship between exclusive breastfeeding and the type of complementary food breastfeeding with the nutritional status of children where the p-values ​​were 0.941 and 0.582, respectively. There was no relationship found between exclusive breastfeeding and the type of complementary food breastfeeding with the nutritional status of children. However, exclusive breastfeeding is further enhanced and provides nutritious complementary food according to the needs of children by utilizing local food sources.